Artificial Mitochondrial Transfer/Transplant to Danio rerio embryos by adapting MitoCeption as a tool to study developmental energetics - Espinosa Vallejo, Roberto Iván (2023)
Mitochondria are responsible for metabolic balance and homeostasis in cells, regulating energy, cell aging, and apoptosis. By fulfilling such important functions, damaged mitochondria can cause acquired or hereditary pathologies that could compromise the independence or survival of the organism. Given this problem, it is of utmost importance to develop methodologies to understand mitochondrial transplant better and reach new therapeutic techniques, such as mitochondrial replacement therapies (MRT), coincubation, Magnetomitotransfer, and MitoCeption. Within the various existing methodologies, MitoCeption stands out for its simplicity and innovative procedure, which consists of a coincubation modification by incorporating centrifugation and heat shock. This research seeks to adapt Mitoception in a new animal model, Danio rerio. Human-zebrafish mitochondrial xenotransplantation was executed because it facilitates obtaining mitochondria and their identification in the recipient organism. Danio rerio was selected because it allows constant monitoring thanks to its transparent tissue and short development timeline. First, the optimal conditions for the fundamental parts of MitoCeption were set. For centrifugation: 50, 100, 300, 500, 1000 RCF; for the medium: E2 and RPMI; and heat shock (4ºC-37ºC). Secondly, MitoCeption was carried out in D. rerio embryos, at 500 RCF in RPMI, with a thermal shock of 4º C to 37 ºC. Finally, the results were analyzed with fluorescence microscopy. All experiments and analyses were carried out during the last semester of 2019 and the first trimester of 2020. Through our study, we seek to broaden the comprehension of mitochondrial transplantation and foster the development of new methods to achieve it.